Deciphering honey trapping crime cases in India = Entschlüsselung von Honey-Trapping-Kriminalitätsfällen in Indien - Prakash, Pranav (Kriminologie - das Online-Journal, 2024)
The presence of Honey-trapping in different forms dates back to the time of ancient kingdoms and empires and involves utilizing romantic or personal connections as a means of obtaining knowledge or power. Honey-trapping crimes have taken on new dimensions in the modern period, particularly in the cyber world, where profiles on social media sites like Facebook and Twitter are used to befriend and then seduce targets into disclosing important information. This behaviour has become a serious problem that jeopardises personal safety and national security. This studyanalyses the honey-trapping Crime Cases to interrogate the methods and implication strategies of honey-trapping, highlighting its transition from physical seduction to digital manipulation. It also scrutinizes the legal and ethical challenges posed by honey-trapping, emphasizing the lack of robust legal mechanisms to address these crimes. Furthermore, the paper discusses preventive measures to equip individuals and organisations against such threats.